Synthesis of carbazoles and related heterocycles from sulfilimines by intramolecular C−H aminations - Tian, Xianhai; Song, Lina; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2020)
While direct nitrene insertions into C−H bonds have become an important tool for building C−N bonds in modern organic chemistry, the generation of nitrene intermediates always requires transition metals, high temperatures, ultraviolet or laser light. We report a mild synthesis of carbazoles and related building blocks through a visible light-induced intramolecular C−H amination reaction. A striking advantage of this new method is the use of more reactive aryl sulfilimines instead of the corresponding hazardous azides. Different catalysts and divergent light sources were tested. The reaction scope is broad and the product yield is generally high. An efficient gram-scale synthesis of Clausine C demonstrates the applicability and scalability of this new method.
Gesehen am 02.09.2020